USING OF ENGLISH IN DIGITAL DA’WAH IN ISLAMIC EDUCATION IN THE ERA OF COVID-19 - Elihami, Elihami; Rusli, Hildayani (Al-Mirah: Jurnal Pendidikan Islam, 2020)
This article discusses preaching through the media or the Internet using English. Fast-growing Media around the world using universal language is English. English is an important global language in all aspects of daily life. Included in the field of Da’wah. Da’wah is the obligation of Islamic Ummah. Da’wah is the submission of Islamic teachings to be practiced in everyday life sourced from Hadith and al-Quran. The importance of the use of English in the millennial language is English bases facilitate the delivery of Islamic teachings to audiences that English as the first language or the original language. In addition, English as an intermediate language in the completion of religious conflict.